Fuzzy Robust Modification Design of EMU Transmission Gear - Ziqiang Sheng; Yuedong Wang; Xiaoning Bai; Shenxuan Wang (Jixie chuandong)
Considering that the modification parameters and performance parameters of gear are affected by various influencing factors during manufacturing and operation process， a robust modification design method for EMU transmission gears based on improved tolerance model and fuzzy theory is proposed. The controllable and uncontrollable factors in gear robust modification are firstly determined， and then the sample points are obtained by combining orthogonal experimental design and Romax motion simulation. The polynomial response surface model is used to fit the response surface function of peak-to-peak value of transmission error. On this basis， the fuzzy theory is introduced， the mathematical model of gear modification robust optimization is established based on improved tolerance model， the NSGA-III algorithm is used to find the optimal solution， and the comparison with other modification schemes is completed. Finally， the simulation verification of each modification scheme is carried out. The results show that the robust modification result based on the improved tolerance model is better than the traditional tolerance model. Considering the influence of fuzzy factors in the design of gear robust modification based on the improved tolerance model， it is not only improves the offset load condition of the tooth surface， but also improves the robustness and rationality of the modification results.